An Education in Facebook - Allen, Matthew (Digital Culture & Education, 2012)
For some years academics have debated the role in higher education of Facebook, the world’s mostextensive social networking site. At first there was enthusiasm—it was a new tool that could be‘repurposed’ for education; then, as Facebook became more widespread, its use seemed less thanopportune. But now, with so many students already engaged before they even come to a university,perhaps it is impossible to avoid the conclusion that Facebook is as natural to education as thecommute, the computer, and everything else which students ‘bring’. This paper first presents a summary of what Facebook affords, by way of its design and use, for online communication and networking, demonstrating the central role of reciprocal acts of attention exchange in this system. It then analyses, through a critical reading of research into Facebook and education, the way Facebook challenges traditional understandings of university education and the relationships between teachers and students. It concludes that, however we might seek to use Facebook in higher education (and there are many reasons we might), its use will always be shaped by—and indeed give rise to—a blurring of the traditional boundaries between formal and informal education.